The Effect of Foreign Ownership, Bonuses, and Company Size on Transfer Pricing - Isdiputra, Feisal; Pangestuti, Irene Rini Demi (LifeSciFi, 2024)
This study aims to analyze the influence of foreign ownership, bonuses, and company size on a company's decision to use transfer pricing. The research was conducted on 185 manufacturing companies listed on the Indonesia Stock Exchange during the 2019–2023 period. The approach used is a quantitative descriptive method. The results show that bonuses have a negative effect on performance, with a negative coefficient value of -0.003. This indicates that providing bonuses may reduce a company's tendency to use transfer pricing as a strategy. Meanwhile, foreign ownership also has a small negative impact on transfer pricing decisions, with a coefficient value of -0.006 and a significance level of 0.482, indicating an insignificant effect. On the other hand, company size is found to have a significant positive impact on transfer pricing, with a coefficient value of 0.743 and a highly significant level of 0.000. This study provides insights that company size is the dominant factor influencing transfer pricing decisions, while the effects of bonuses and foreign ownership are relatively small and insignificant. These findings contribute to a better understanding of the factors influencing transfer pricing practices in manufacturing companies in Indonesia.